رقص کی شرعی حیثیت:فقہاء کے افکار کا مطالعہ (Al-Qamar, 2023)
Dance relates to “Fine Arts", a branch of contemporary Sciences and is considered to be favorite type of arts amongst moderate mentality all over the world. However, in Islam, dance is not considered a positive thing for humanity, as its results are undesirable, especially the “women’s dance” before the “men” which is considered to be the worst kind of dance. The eventual result of this kind of dance is often vulgarity, nakedness and other unfavorable things prohibited in Islam. Most of the Jurists of each school of thought are of the opinion that dance is prohibited act (haram) in Islam and orthodox ulamas of every age remark it as a vital sin. This research paper is a critical study of different approaches of Muslim scholars. Some opposing thoughts like Imam Ibn-e-Jozi and Ibn-e-Taymia, some favoring views like opinion of Ghazali and some opinions keeping in view the circumstances, motives and situations for prohibiting, allowing or considering it the natural act, have been discussed in detail to find the Islamic approach about this act which is considered to be the mean of entertainment, spiritual progress or just wastage of the sources and time amongst the different classes of the society. This research paper is a study to analyze that which kind of dance is prohibited in Islam and which types is allowed or is not considered to be a sin Islam.